Relationship Dynamics of Couples Facing Advanced-Stage Parkinson’s Disease: A Dyadic Interpretative Phenomenological Analysis - Constant, Emilie; Brugallé, Elodie; Wawrziczny, Emilie; Sokolowski, Céline; Manceau, Charlotte; Flinois, Bérengère; Baille, Guillaume; Luc, Defebvre; Dujardin, Kathy; Antoine, Pascal (Frontiers in Psychology, 2022)
Background/objective: Several studies have examined the impact of Parkinson's disease (PD) on the quality of couples' relationships. To date, few studies have explored how couples experience their couple dynamic by taking into account the stage of the disease. The objectives of this study were to understand the experience of each partner and to study the mechanisms that underlie their couple organization in the advanced stage of PD. Method: Semistructured individual interviews conducted with fifteen patients and their partners were the subject of a dyadic interpretative phenomenological analysis. Results: Three themes were identified from the analysis: the first, "A closeness that separates", allows the identification of different patterns of interactions that lead to emotional distancing between the partners; the second, "The adversity is not unbearable, but going it alone would be", emphasizes the importance of how the assisting partner goes about providing support; and the third, "Be prepared for anything and facing an uncertain future", reveals the extent and modes of the dyadic regulation of the emotions linked to what the future may hold. Conclusion: Psychological support is important to help couples express both their feelings and their respective needs in the evolving context of PD.